Utilization of E-Learning as Media in Indonesian Language Courses in Higher Education Post COVID-19 Pandemic - Andi Febri Herawati; Alfitriani Siregar; Yusrizal Yusrizal; Anita Ade Rahma; Avid Leonardo Sari; Irwandi Irwandi (AL-ISHLAH: Jurnal Pendidikan, 2021)
The rapid development of technology has increased the demand for information technology-based learning media, which is becoming increasingly necessary. E-Learning, also known as information technology-based learning media, is changing how education is delivered from a traditional to a digital format. At this time, the world is being affected by the COVID-19 pandemic, which is causing restrictions on activities and gatherings and causing difficulties in lectures. Electronic learning, the most widely used learning medium by all groups, is seen as a solution to keep the learning going in higher education, from primary to post-secondary levels of education. The purpose of this study was to investigate the use of E-Learning as a learning medium in the Indonesian language education department of universities following the outbreak of the COVID-19 pandemic. This study uses a qualitative approach with descriptive analysis to implement Indonesian language education learning by taking samples from lecturers who teach Indonesian courses at the Manado State Islamic Institute and Manado State Christian Institute. According to the study's findings, using information technology as a medium of learning in Indonesian language education courses through e-learning is beneficial, particularly in light of the country's ban on face-to-face instruction. Then, the university should continue to develop e-learning to improve the ease and quality of the teaching and learning process, increase student learning effectiveness, and broaden its reach.